Actuator failure compensation-based command filtered control of electro-hydraulic system with position constraint. (March 2023) - Phan, Van Du; Truong, Hoai Vu Anh; Ahn, Kyoung Kwan
Abstract: In this article, the design and experimental evaluation of a fault-tolerant controller are introduced for a double-rod electro-hydraulic actuator subjected to actuator faults and disturbances. The internal leakage fault is captured as a bias fault, whilst the faults in servo-valve and supply failure are considered as a partial loss of effectiveness (LOE) fault. The design obstacles caused by the disturbances and bias fault are suppressed by nonlinear disturbance observers (NDO) while an asymmetric barrier Lyapunov function is used to ensure the non-violated boundary of the output position. To tackle the LOE fault, the development of an enhanced adaptive compensation technique for actuator fault-tolerant control (FTC) is then constructed. Moreover, to mitigate the "explosion of complexity" in the traditional backstepping design, the command-filtered control is utilized to elaborate the FTC scheme. It is shown by theoretical analysis that system stability is ensured under faulty conditions. Finally, simulation/experiment results and comparison studies are performed to further verify the effectiveness of the proposed approach. Highlights: The lumped disturbances, bias fault and a partial LOE faults is firstly considered for EHA. The NDOs and an enhanced adaptive law is developed to tackle bias fault and LOE fault. The proposed FTC method based on CFC approach and BLF is performed. The stability of the closed-loop system is ensured based on the Lyapunov theory. Comparative experimental results confirm the effectiveness of the proposed controller.